2018
DOI: 10.1200/cci.17.00128
|View full text |Cite
|
Sign up to set email alerts
|

Automated Extraction of Grade, Stage, and Quality Information From Transurethral Resection of Bladder Tumor Pathology Reports Using Natural Language Processing

Abstract: Purpose Bladder cancer is initially diagnosed and staged with a transurethral resection of bladder tumor (TURBT). Patient survival is dependent on appropriate sampling of layers of the bladder, but pathology reports are dictated as free text, making large-scale data extraction for quality improvement challenging. We sought to automate extraction of stage, grade, and quality information from TURBT pathology reports using natural language processing (NLP). Methods Patients undergoing TURBT were retrospectively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…NLP for the analysis of radiology reports has also been explored in the context of other cancer types, including hepatocellular carcinomas, [13][14][15][16] breast cancer, [17][18][19][20] lung cancer, [21][22][23] and other abdominal or pelvic tumors. 11,[24][25][26][27] All studies that provided sufficient insight into their modeling approach used a bag-of-words approach. To our knowledge, this study presents the first sequence-based NLP approach for analyzing free-text radiology reports in oncology patients as well as the first head-to-head comparison of sequence-based and bag-of-words models for medical text analysis.…”
Section: Discussionmentioning
confidence: 99%
“…NLP for the analysis of radiology reports has also been explored in the context of other cancer types, including hepatocellular carcinomas, [13][14][15][16] breast cancer, [17][18][19][20] lung cancer, [21][22][23] and other abdominal or pelvic tumors. 11,[24][25][26][27] All studies that provided sufficient insight into their modeling approach used a bag-of-words approach. To our knowledge, this study presents the first sequence-based NLP approach for analyzing free-text radiology reports in oncology patients as well as the first head-to-head comparison of sequence-based and bag-of-words models for medical text analysis.…”
Section: Discussionmentioning
confidence: 99%
“…24 Glaser and colleagues report an NLP approach to bladder cancer pathology showing concordance of 0.82 for stage, 1.00 for grade, and 0.81 for muscularis propria invasion. 25 Thomas et al 26 reported the use of a rule-based NLP system to identify patients with prostate cancer from prostate biopsy reports and extract Gleason scores, percentage of tumor involved, and presence of atypical small acinar proliferation (ASAP), high-grade prostatic intraepithelial neoplasia (HGPIN), and perineural invasion, with accuracy between 94% and 100% in a sample of 100 reports. They also extract information from 100 radical prostatectomy pathology reports to identify detailed pathologic features with 95% to 100% accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…28 Our work, using a rule-based NLP approach, achieved similar results to other nvestigators. 24,25,29 However, instead of comparing results to only manual abstraction in a test environment, we report results from a real-world clinical implementation and compare with both manual abstraction and clinician-entered SDEs at the point of care. Our parallel approach has several advantages.…”
Section: Discussionmentioning
confidence: 99%
“…GRADE: appearance of the cancerous cells [8], [52], [9], [48], [87], [26] INVASION: whether or not more than 50% of an organ is invaded [52], [88] SIZE: quantitative size of tumor (e.g., 2.2 x 2.0 cm), diameter/volume of the tumor, including unit (e.g., 1 cm, 0.3 x 0.5 x 0.7 cm) [13], [52], [88], [85], [42], [25], [48], [41] SIZE TYPE: radiological/pathological [25] NEGATION: indicator to some negation of a tumor reference (e.g., no) [85], [86], [41] COUNT: number of tumor/nodule references (e.g., two or multiple) [13], [88], [85] TUMOR REFERENCE: a radiologic artifact that may reference a tumor (e.g., lesion or focal density) [88], [85] MENTION: tumor major object (e.g., tumor, lesion, mass, and nodule) [13], [42], [47], [49], [41] QUANTIFIER: one, two, three, several [42] TEMPORAL INFORMATION: refers to information about time (e.g., year, month, and date, 2007-08-04) [52], [42], [86] NON-TUMOR SIZE ITEMS: LeVeen needle, which is used in RFA treatment [42] STATUS: this indicates the final overall tumor status (e.g., regression, stable, progression, irrelevant) [89], [41] METASTATIC STATUS INDICATORS: phrases denoting a metastatic tumor [9], [90] MAGNI...…”
Section: Frame Elements Referencesmentioning
confidence: 99%